10.1016/s0029-7437(09)70335-0 (CrossRef Listing of Deleted DOIs, 2000)
Background Children with disabilities (e.g., with autism spectrum disorder or wheelchair use due to a physical disability) face challenges in participating in daily life. These participation barriers are the result of limiting influences present in both the child's social and physical environments. Parents play a key role in creating environments that facilitate their child's participation. The aim of this study is to explore in depth how parents of children with disabilities make sense of their thoughts, feelings and concerns as they reflect on their strategies, challenges and needs with a focus on how they facilitate their children's participation. Methods Nine parents of children with disabilities were interviewed. Interviews were transcribed verbatim and analysed using interpretative phenomenological analysis. Results Four major themes emerged from the analysis: (1) parents' experiences and concerns with systems and regulatory frameworks, (2) parents' feelings and concerns about the child's school life, (3) parents' efforts and thoughts while promoting their child's leisure activities and social relationships and (4) parents' emotional experiences and concerns in shaping family life. Parents experience difficulties in finding tailored care, education and leisure activities for their child and they search for appropriate assistance, schools and leisure activities. Conclusions This study provides an in-depth exploration of how parents articulate and make sense of their experiences. Parental strategies, challenges and needs emerge within both social and physical environments. Parents reported barriers to inclusion and expressed a need for tailored support to enhance their child's participation. The findings underscore the importance of integrating parental knowledge into shaping policy and practice.